Identification and characterization of tsunami deposits off southeast coast of India from the 2004 Indian Ocean tsunami: Rock magnetic and geochemical approach - Veerasingam, S.; Venkatachalapathy, R.; Basavaiah, N.; Ramkumar, T.; Venkatramanan, S.; Deenadayalan, K. (My University, 2014)
The December 2004 Indian Ocean Tsunami (IOT) had a major impact on the geomorphology and sedimentology of the east coast of India. Estimation of the magnitude of the tsunami from its deposits is a challenging topic to be developed in studies on tsunami hazard assessment. Two core sediments (C1 and C2) from Nagapattinam, southeast coast of India were subjected to textural, mineral, geochemical and rock-magnetic measurements. In both cores, three zones (zone I, II and III) have been distinguished based on mineralogical, geochemical and magnetic data. Zone II is featured by peculiar rock-magnetic, textural, mineralogical and geochemical signatures in both sediment cores that we interpret to correspond to the 2004 IOT deposit. Textural, mineralogical, geochemical and rock-magnetic investigations showed that the tsunami deposit is featured by relative enrichment in sand, quartz, feldspar, carbonate, SiO 2, TiO 2, K 2O and CaO and by a depletion in clay and iron oxides. These results point to a dilution of reworked ferromagnetic particles into a huge volume of paramagnetic materials, similar to what has been described in other nearshore tsunami deposits (Font et al. 2010). Correlation analysis elucidated the relationships among the textural, mineral, geochemical and magnetic parameters, and suggests that most of the quartz-rich coarse sediments have been transported offshore by the tsunami wave. These results agreed well with the previously published numerical model of tsunami induced sediment transport off southeast coast of India and can be used for future comparative studies on tsunami deposits.
Keywords: Tsunami deposit; Texture size; Mineral; Geochemistry; Rock magnetism; Indian ocean tsunami